VALUE CREATION IN E-BUSINESS: A STUDY OF TWO B-TO-B COMPANIES - Efendi Efendi (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
The current study analyzes the study of Amit and Zott (2001) using the nowadays business practices in two B-to-B companies. The companies utilize value constellations strategies in conducting their business. They re-create values for their business customers. The study intends to find new sources of value creation not discovered in Amit and Zott (2001). Amit and Zott (2001) argue that the sources of value creation in e-business are efficiency, complementarities, lock-in, and novelty. The research uses in-depth interview as a tool in qualitative methodology. Two interviews were conducted on the executives from two e-business companies providing services to other companies in the value chain. After analyzing the data, it was found that, there are two new sources of value creation in e-business, which are the value of information and digital ecosystem. The new findings in this research could be due to the focus of Amit and Zott (2001) on B-to-C customers and the absence of fully-fledged digital ecosystem seen in today’s digital platforms.